Techniques and Philosophy Steps of Ampek Sasaran Junguik Sati: In the Context of Minangkabau Culture - Metro, Wardi; Stevenson, Yan; Maghfirah, Auliana Mukhti (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research aims to investigate the technique and philosophy behind Step Ampek Sasaran Junguik Sati in the context of Minangkabau culture. Langkah Ampek is a traditional movement in Minangkabau martial arts that has been passed down from generation to generation. This research uses a qualitative approach by collecting data through direct observation, interviews with skilled practitioners, and analysis of related cultural texts. The results showed that Langkah Ampek is not only a series of physical movements, but also reflects philosophical values in Minangkabau culture. The philosophy includes spiritual, moral, and social aspects, which are reflected in each step of the movement. The techniques used in the Langkah Ampek Sasaran Junguik Sati are closely related to natural conditions, daily life, and the history of Minangkabau culture. This research also identified that Sasaran Junguik Sati plays an important role in maintaining Minangkabau cultural identity and strengthening the sense of solidarity among community members. The practical implication of this research is the importance of maintaining and developing traditional cultural heritage as an integral part of cultural sustainability and community development in Minangkabau.